2022
DOI: 10.3390/ijms23095255
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding the Gene-Specific Roles of GATA Factors in Heart Development: Does GATA4 Lead the Way?

Abstract: Transcription factors play crucial roles in the regulation of heart induction, formation, growth and morphogenesis. Zinc finger GATA transcription factors are among the critical regulators of these processes. GATA4, 5 and 6 genes are expressed in a partially overlapping manner in developing hearts, and GATA4 and 6 continue their expression in adult cardiac myocytes. Using different experimental models, GATA4, 5 and 6 were shown to work together not only to ensure specification of cardiac cells but also during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…Many cardiac-specific genes possess GATA elements in their regulatory regions, including not only structural sarcomere genes, such as myosin light chain-3 (MYL3) or troponin C (TNNC1) and I (TNNI3), but also genes for Na + /Ca 2+ -exchanger (SLC8A3), acetylcholine receptor-M2 (CHRM2), cardiac-restricted ankyrine repeat protein (CARP), carnitine palmitoyltransferase-1b (CPT1B), and other transcription factors, such as NKX2-5, which have been shown to be regulated by GATA4 [52]. Due to the overlap in the DNAbinding region, the cardiac subfamily of GATA transcription factors (GATA4/5/6) exhibit redundant functions and interact with each other to ensure the specification of cardiac cells and subsequent heart development [53].…”
Section: Gata4 In Cardiomyocyte Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cardiac-specific genes possess GATA elements in their regulatory regions, including not only structural sarcomere genes, such as myosin light chain-3 (MYL3) or troponin C (TNNC1) and I (TNNI3), but also genes for Na + /Ca 2+ -exchanger (SLC8A3), acetylcholine receptor-M2 (CHRM2), cardiac-restricted ankyrine repeat protein (CARP), carnitine palmitoyltransferase-1b (CPT1B), and other transcription factors, such as NKX2-5, which have been shown to be regulated by GATA4 [52]. Due to the overlap in the DNAbinding region, the cardiac subfamily of GATA transcription factors (GATA4/5/6) exhibit redundant functions and interact with each other to ensure the specification of cardiac cells and subsequent heart development [53].…”
Section: Gata4 In Cardiomyocyte Differentiationmentioning
confidence: 99%
“…The endocardium and endocardial cushions have a high expression of the transcription factor, and it was shown that GATA4 mediates both epithelial-to-mesenchymal transition (EMT) in the endocardial cushions and the growth and remodeling of the atrioventricular cushions, playing an important role in valve development [57]. Furthermore, GATA4 interacts with different cofactors in order to promote cell-type-specific gene expression programs [53]. For example, Kim et al demonstrated the interaction between GATA4 and RERE (arginine-glutamic acid dipeptide repeats gene), a cardiac-expressed nuclear receptor co-regulator, in the development of the membranous portion of the ventricular septum, via their effects on EMT and mesenchymal cell proliferation [58].…”
Section: Gata4 In the Development Of The Atrioventricular Regionmentioning
confidence: 99%
“…Recent aggregating evidence has underscored the key roles of some nuclear transcriptional factors in regulating proper cardiovascular morphogenesis, including the guanine-adenine-thymine-adenine (GATA) family of transcriptional factors ( 2 , 51 , 76 ). At present, six members of the GATA family have been categorized fundamentally into a cardiac subfamily (GATA4/5/6) and a hematopoietic subfamily (GATA1/2/3) ( 76 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent aggregating evidence has underscored the key roles of some nuclear transcriptional factors in regulating proper cardiovascular morphogenesis, including the guanine-adenine-thymine-adenine (GATA) family of transcriptional factors ( 2 , 51 , 76 ). At present, six members of the GATA family have been categorized fundamentally into a cardiac subfamily (GATA4/5/6) and a hematopoietic subfamily (GATA1/2/3) ( 76 ). GATA4 and GATA6 , as well as GATA5 , are among the first genes expressed abundantly in the embryonic heart with a partially overlapping mode of expression spectrum, and these three cardiogenic GATA factors regulate cardiac organogenesis ( 76 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation